La Corte Penal Internacional y las legislaciones nacionales: relación entre Derecho internacional y Derechos nacionales. I. Legislación internacional - Odello , Marco (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2004)
The entry into force of the Statute of the International Criminal Court represents an important development for the prosecution of international crimes committed by individuals. The Court has jurisdiction over violations related to both human rights and humanitarian law, but the Court has a complementary jurisdiction in relation to national courts. The aforementioned issues imply relevant relations between international and national law, mainly in criminal matters, which are usually reserved to national jurisdiction. In this paper we present some issues related to this complex relationship.